2022
DOI: 10.1093/bioinformatics/btac708
|View full text |Cite
|
Sign up to set email alerts
|

HaploDMF: viral haplotype reconstruction from long reads via deep matrix factorization

Abstract: Motivation Lacking strict proofreading mechanisms, many RNA viruses can generate progeny with slightly changed genomes. Being able to characterize highly similar genomes (i.e. haplotypes) in one virus population helps study the viruses’ evolution and their interactions with the host/other microbes. High-throughput sequencing data has become the major source for characterizing viral populations. However, the inherent limitation on read length by next-generation sequencing (NGS) makes complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…In addition of HairSplitter, we chose to evaluate the software stRainy (Kazantseva et al, 2023) and Strainberry (Vicedomini et al, 2021), which have been introduced specifically as bacterial strain separation methods, hifiasm-meta (X Feng et al, 2022), which is the most popular assembler for direct HiFi assembly, Strainline (X Luo et al, 2022) and HaploDMF (Cai et al, 2022), which have been introduced as viral strain separation methods and finally iGDA (Z Feng et al, 2021), which can perform both.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition of HairSplitter, we chose to evaluate the software stRainy (Kazantseva et al, 2023) and Strainberry (Vicedomini et al, 2021), which have been introduced specifically as bacterial strain separation methods, hifiasm-meta (X Feng et al, 2022), which is the most popular assembler for direct HiFi assembly, Strainline (X Luo et al, 2022) and HaploDMF (Cai et al, 2022), which have been introduced as viral strain separation methods and finally iGDA (Z Feng et al, 2021), which can perform both.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of bacterial strain separation, Vicedomini et al, 2021 showed that mainstream assemblers such as metaFlye (Kolmogorov et al, 2020) and Canu (Koren et al, 2017) failed to distinguish close bacterial haplotypes and proposed a new tool, called Strainberry, to reconstruct strains. In the context of viral strain separation, Strainline (X Luo et al, 2022) and HaploDMF (Cai et al, 2022) were presented to tackle specifically the viral haplotype reconstruction problem and need very high depth of sequencing to work. The method iGDA (Z Feng et al, 2021) was proposed as a general approach to phase minor variants while handling high error rates and could theoretically assemble both bacterial and viral haplotypes.…”
Section: Introductionmentioning
confidence: 99%
“…This study aimed to assess the accuracy, performance, and computational efficacy of seven candidate long-read assemblers, categorized into two approaches for haplotype reconstruction: (1) de novo long-read assemblers, which include Canu, 47 Goldrush, 48 MetaFlye, 42 and Strainline, 28 and (2) reference-based long-read assemblers, which comprise HaploDMF, 43 iGDA, 44 and RVHaplo. 45 The assembly software, including Canu, MetaFlye, and iGDA, was installed using the Micromamba package manager, which utilized recipes from the conda-forge (https://anaconda.org/conda-forge) and bioconda channels (https://anaconda.org/bioconda).…”
Section: Long-read Assemblersmentioning
confidence: 99%
“…28,42 HaploDMF, iGDA, and RVHaplo are reference-based assemblers designed for multi-strain mixtures. [43][44][45] iGDA and RVHaplo employ similar clustering approaches, while HaploDMF uses deep matrix factorization for contig extension. 43,46 Despite numerous assembly software options tailored for SMS data, 28,[42][43][44][45]47,48 selecting the best tool for haplotype reconstruction and HIV-1 quasispecies analysis is challenging due to a lack of systematic studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation